(Bio)chemical reactions associated with ageing of red kidney beans (Phaseolus vulgaris) during storage probed by volatile profiling: The role of glass transition temperature. (December 2022) - Wainaina, Irene; Kyomugasho, Clare; Delbaere, Sophie; Wafula, Elizabeth; Van Loey, Ann; Sila, Daniel; Hendrickx, Marc
Graphical abstract: Highlights: (Bio)chemical reactions during storage of red kidney beans were related to Tg . Evolution of volatile compounds was influenced by storage conditions. Marker compounds identified are typical for protein degradation and lipid oxidation reactions. Kinetics of marker compounds highly correlated with storage above Tg . The nature, rate and extent of storage-induced (bio)chemical reactions can be controlled by Tg . Abstract: During storage, common beans are susceptible to ageing leading to quality changes, in particular their cooking quality. In this study, kinetics of evolution of volatile compounds was assessed in order to gain insight into possible reactions occurring during ageing of beans. The evolution of volatile compounds of red kidney beans stored at varying conditions of temperature and moisture content relative to their glass transition temperature (Tg ) were evaluated. Storage conditions highly influenced the evolution of volatile compounds whereby more volatile compounds and higher concentrations were detected in beans stored at higher temperature and moisture content. The volatile marker compounds identified are typical for protein degradation and lipid oxidation reactions, although for beans stored at the highest moisture contents (12.8 and 14.5%) the compounds obtained do not allow to exclude microbial activity. The rate of evolution of selected volatile marker compounds was highly correlated (benzaldehyde (r = 0.58), acetic acid (r = 0.75), 1-propanol, 2-methyl (r = 0.84) and 2-butanone (r = 0.89)) with storage above Tg signifying that the rate and extent of these (bio)chemical reactions can be largely controlled by storing the beans at temperatures not exceeding 20 °C above their Tg . Volatile profiling showed to be an important approach to monitor quality changes of beans during storage by assessing the nature, rate and extent of (bio)chemical reactions occurring.